2016
DOI: 10.1136/bmj.i4338
|View full text |Cite
|
Sign up to set email alerts
|

External validation of prognostic models to predict risk of gestational diabetes mellitus in one Dutch cohort: prospective multicentre cohort study

Abstract: ObjeCtiveTo perform an external validation and direct comparison of published prognostic models for early prediction of the risk of gestational diabetes mellitus, including predictors applicable in the first trimester of pregnancy. DesignExternal validation of all published prognostic models in large scale, prospective, multicentre cohort study. setting 31 independent midwifery practices and six hospitals in the Netherlands. PartiCiPantsWomen recruited in their first trimester (<14 weeks) of pregnancy between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
88
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 47 publications
8
88
0
4
Order By: Relevance
“…In the present study, important novel findings are reported for a risk factor scoring system for identifying women most at risk of GDM in a Chinese population. Though the present cohort displays risk factors similar to those identified previously, 20 the relationship of these risks to GDM among a southern Chinese population in a quickly developing urban region has not been widely studied; the demographics of the present population, including the low mean BMI, reinforce the need for population-specific approaches to assessing and treating GDM. The high percentage of GDM diagnoses captured by these risk factors and the similarities in the receiver operating characteristic curves between the validation and derivation cohorts are promising indicators of the capabilities of such a screening approach.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In the present study, important novel findings are reported for a risk factor scoring system for identifying women most at risk of GDM in a Chinese population. Though the present cohort displays risk factors similar to those identified previously, 20 the relationship of these risks to GDM among a southern Chinese population in a quickly developing urban region has not been widely studied; the demographics of the present population, including the low mean BMI, reinforce the need for population-specific approaches to assessing and treating GDM. The high percentage of GDM diagnoses captured by these risk factors and the similarities in the receiver operating characteristic curves between the validation and derivation cohorts are promising indicators of the capabilities of such a screening approach.…”
Section: Discussionsupporting
confidence: 53%
“…For each factor, a weight was obtained by multiplying the β-coefficient from the multivariate logistic regression model by 10 and then rounding it to the nearest integer. 20 The performance of the scoring system was further examined using the INTERGROWTH-21st standards for weight gain during pregnancy. The performance of this scoring system for the prediction of GDM was evaluated by calculating the sensitivity, specificity, and positive and negative predictive values and their 95% confidence intervals (CIs) at different risk score cutoffs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the results for BMI and ethnicity prompted us to make a comprehensive assessment of GDM risk. A number of risk evaluation models have been proposed and validated, which was of great value in identifying the high‐risk population . Based on our findings we recommend screening and interventions for the truly high‐risk population by a thorough risk evaluation model, rather than simply using BMI as a guide.…”
Section: Discussionmentioning
confidence: 99%
“…For several common complex diseases, including different forms of cancer, diabetes, and cardiovascular disease, many prediction models have been developed in various source populations [1][2][3][4][5][6][7]. The predictive performance of these risk models is typically assessed by evaluating discrimination.…”
Section: Introductionmentioning
confidence: 99%